2020
DOI: 10.1101/2020.10.26.20209361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Economic and social impacts of COVID-19 and public health measures: results from an anonymous online survey in Thailand, Malaysia, the United Kingdom, Italy and Slovenia

Abstract: In the absence of a vaccine and widely available treatments for COVID-19, governments have relied primarily on non-pharmaceutical interventions to curb the pandemic. To aid understanding of the impact of these public health measures on different social groups we conducted a mixed-methods study in five countries ('SEBCOV' - Social, ethical and behavioural aspects of COVID-19). Here we report the results of the SEBCOV anonymous online survey of adults. Overall, 5,058 respondents from Thailand, Malaysia, the Uni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Here we describe results from a qualitative study, which was part of a mixed-methods study (SEB-COV) that also included an online survey [29]. The quantitative results are reported elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we describe results from a qualitative study, which was part of a mixed-methods study (SEB-COV) that also included an online survey [29]. The quantitative results are reported elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence also suggests that the use of NPIs in the context of COVID-19 has had unequal effects on society, including across and within countries. For example, a survey comparing the impact of NPIs in Thailand, Malaysia, Italy, Slovenia and the UK found that those living in lower income countries reported more severe economic impact during the first wave of COVID-19 restrictions [11]. Another survey conducted among 17 countries in Latin America and the Caribbean found that the poorest households reported the highest levels of job loss and household food insecurity and that these impacts were also substantially higher among countries with mandatory NPIs, such as quarantines, curfews and mobility restrictions, compared to countries not implementing such restrictions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Here we describe results from a qualitative study, which was part of a mixed-methods study (SEB-COV) that also included an online survey [28]. The quantitative results are reported elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence also suggests that the use of NPIs in the context of COVID-19 has had unequal effects on society, including across and within countries [11, 12]. Vulnerable populations in particular, including migrants, people working in the informal economy, homeless people, older people and people living with disabilities, may be disproportionately affected by the adverse impacts of NPIs [7, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Closure of schools and working from home have impacted business operations, with a consequent decrease in the demand for commodities. In Malaysia, like other countries around the world, the COVID-19 pandemic has caused catastrophic economic and social disruptions [5][6][7]. The distancing measures, together with employment and financial insecurity, represent a massive mental health crisis affecting the wellbeing of populations throughout the world [8].…”
Section: Introductionmentioning
confidence: 99%